School Family Partnerships in Moral Character Development: A Case Study of Islamic Religious Education in Indonesia - Anita. S; H.M. Nasri Hamang; Suredah Hamid; H.M. Nasir; Andi Muis (CV. Gerasi Insan Nusantara, 2026)
The development of students’ moral character has become a critical concern in contemporary education due to increasing social and moral challenges among young learners. This study aims to explore the collaboration between Islamic Religious Education (IRE) teachers and parents in shaping students’ moral character at UPT SDN 2 Kalosi, Enrekang Regency, Indonesia. Employing a qualitative case study approach, data were collected through observations, in-depth interviews, and document analysis involving the principal, IRE teachers, classroom teachers, and parents. The data were analyzed using the interactive model of data reduction, data display, and conclusion drawing, while triangulation techniques were applied to ensure trustworthiness. The findings reveal that effective moral character development is achieved through continuous communication between teachers and parents, parental involvement in character-based assignments, alignment of moral values between school and home, and active support for school programs. The integration of school-based moral education and family parenting practices contributes significantly to the development of honesty, discipline, responsibility, empathy, and social awareness among students. However, challenges remain, including limited parental time, inconsistent communication, differences in parenting styles, and varying levels of parental participation. The study implies that sustainable school–family partnerships are essential for strengthening students’ moral character and creating consistency in value internalization across educational environments. The originality of this study lies in its examination of teacher–parent collaboration within the context of Islamic Religious Education at the elementary school level, highlighting how the integration of religious learning strategies and family-based moral guidance can foster holistic character development. The findings contribute to the growing literature on character education by offering a practical model of collaborative moral education that can be adapted in similar educational contexts